The extent of activating educational methods in improving the outcomes of the educational process at the University of Tobruk: The Faculty of Education as a model - العبيدي المبروك ابوبكر امجاور; الطبولي نجوى عبد الكريم (Tobruk University Journal of Social and Human Sciences, 2021)
Educational means are an important pillar of the educational process and the main supporter in achieving development and progress in the information revolution, as the adoption of any educational system is no longer a luxury, but has become a necessity of quality education, Hence, our study aims to identify any preference explanation between the educational medium and the teacher and to identify the negative and positive effects of teaching aids on the teacher and the student, while taking note of the problems that hinder without using them. Likart trio) using the field method with the use of the method of description and analysis, where a random sample size (25%) was distributed to (20 faculty members at the Faculty of Education University of Tobruk) and the study reached to several results, the most important of which were: 1.The results of the study 50% emphasize the provision of teaching aids of effort and time spent during the lesson 2.Most of the study members refer to the positive role of teaching aids in encouraging students in the learning process by (45%). 3.Teaching aids to expand the thinking and the involvement of the senses by (60%) for students learners.